A human behaviour model and its implications in the transport context - Ali Najmi; Travis Waller; Mehrdad Memarpour; Divya Nair; Taha H. Rashidi (Transportation Research Interdisciplinary Perspectives, 2023)
This paper delves into the importance of understanding the psychological and cognitive factors that play a vital role in individuals' decision-making and behaviour when it comes to transport. It recognises that while quantitative-based utilities such as cost and performance are important considerations, they are not the only determinants of behaviour. The paper aims to develop a conceptual perspective of psychological and moral values, societal experiences, and service perception and discuss their implications for individuals’ behaviour in transport contexts. To achieve this, the paper draws on theories and concepts from psychology literature, specifically subjective norms and affective attributes. These are used to explore the contextual dimensions of travellers' behaviour and identify the key factors that influence their behaviour and decisions. Thus, two main contributions of the paper are 1) developing a conceptual model that can be used to analyse the decisions of transport users and predict their behaviour 2) reviewing the implications of these factors in the transport context. In particular, the importance of socio-ethical factors in individuals' behaviour toward using transport services and their possible implications in long-term transport planning is discussed.